CELEBRITY ENDORSEMENT ON COSMETIC PRODUCTS AND ITS IMPACT ON SALES IN JAKARTA - Juliana Berewot (Journal of Business Strategy and Execution, 2018)
The raising demand of cosmetics in Jakarta has created competition in Indonesia’s cosmetics industry both for foreign and domestic companies. As a result, consumers are offered with many options of brands from different companies. This condition creates difficulties both for the customers to recognize the best cosmetic for them and for the companies to attract more consumers to use their products. In order to increase sales and to produce brand awareness, some companies using celebrities as their endorsers. The common reason using celebrities is that the messages carried by celebrities has great impact on customers rather than those carried by non-celebrities. The aim of this research paper is to find out the impact of celebrities endorsement on cosmetic products sales in Jakarta and also to find out the motives of using celebrity endorsement. The finding of this research revealed that celebrity endorsement has influenced consumers’ demand of the products thus it their sales.